0

# -3(5 + -1d) = 2d + 10

help plase

### 3 Answers by Expert Tutors

Kevin F. | Computer Programming and Mathematics TutorComputer Programming and Mathematics Tut...
5.0 5.0 (3 lesson ratings) (3)
3
-3(5 + -1d) = 2d + 10

simplify the expression inside the parentheses
-3(5 - d) = 2d + 10

now remove the parentheses
-15 + 3d = 2d + 10

add 15 to both sides of the equation
3d = 2d + 25

subtract 2d from both sides of the equation
d = 25

To double check, substitute 25 for d in the original equation:
-3(5 + -1(25)) = 2(25) + 10
-3(5 - 25) = 2(25) + 10
-3(-20) = 2(25) + 10
60 = 50 + 10

1
First, distribute -3 to everything in the parentheses: -3(5 + -1d) = -15 + 3d.
You are left with -15 + 3d = 2d + 10.
Next, move like terms to the same side of the equation. You are left with d = 25.

Substitute d = 25 to double check the answer. -3(5 + -1(25)) = 2(25) + 10. Solve everything in parentheses on the left and do the multiplication on the right to get -3(-20) = 50 + 10. This leaves 60 = 60.

Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi Sdgaeth;
-3(5 + -1d) = 2d + 10
Let's distribute...
A negative number multiplied by a negative number is a positive result. Henceforth, (-3)(-1d)=3d...
-15+3d=2d+10
Let's isolate d...
Let's subtract 2d from both sides...
-2d-15+3d=2d+10-2d
-15+d=10
Let's add 15 to both sides...
15-15+d=10+15
d=25

Let's check our results...
-3(5 + -1d) = 2d + 10
-3[(5+(-1)(25)]=[(2)(25)]+10
A negative number multiplied by a positive number is a negative result.  Henceforth, (-1)(25)=-25
-3(5-25)=50+10
-3(-20)=60
60=60